Sodium battery negative electrode material and application thereof

By nitrogen-doping and metal oxide coating of the carbon active material of the sodium-ion battery negative electrode material, a core and shell structure is formed, which solves the problem of many oxygen-containing functional groups on the surface of non-graphite carbon materials and improves the rate performance of the battery. , Coulombic efficiency and cycle performance.

CN119361619APending Publication Date: 2025-01-24HUAWEI DIGITAL POWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310921187.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The non-graphite carbon materials used in existing sodium ion batteries have a large surface oxygen-containing functional groups, resulting in a thick SEI film, affecting rate performance, first-time Coulomb efficiency and cycling performance.

Method used

By nitrogen-doping and metal oxide coating of carbon active materials, a core and shell structure is formed, which reduces surface oxygen-containing functional groups, suppresses interface reactions, and ensures that the SEI film is dense and stable.

Benefits of technology

It achieves good rate performance, high first Coulombic efficiency and good cycle performance of sodium-ion batteries, taking into account conductivity and interface stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361619A_ABST
    Figure CN119361619A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a sodium battery negative electrode material and application thereof. The sodium battery negative electrode material comprises an inner core and a shell layer coated on the inner core, and the inner core comprises a carbon active material doped with a nitrogen element; the shell layer includes a metal oxide. According to the sodium-ion battery negative electrode material, a nitrogen-doped element and a metal oxide coating layer are introduced into a carbon active material, so that a sodium-ion battery adopting the sodium-ion battery negative electrode material has good rate capability, cycle performance and relatively high first coulombic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the technical field of sodium ion batteries, and specifically to a sodium battery negative electrode material and its application. Background Art

[0002] Sodium ion batteries have become one of the research hotspots in the field of energy storage because they use sodium, which is cheaper and more abundant than lithium, and have low production costs. Since the radius of sodium ions is larger than that of lithium ions, sodium ions cannot be embedded in graphite interlayers to form compounds like lithium ions, so non-graphite carbon materials (such as soft carbon or hard carbon) with large interlayer spacing are usually used as negative electrode materials in sodium ion batteries. However, the surface of non-graphite carbon materials usually has a large number of oxygen-containing functional groups, which increases the consumption of electrolyte and active sodium, and causes the SEI film (solid electrolyte interface) formed on the negative electrode surface to be thicker, resulting in poor rate performance of the battery, low first coulomb efficiency, poor cycle performance, etc. At present, no effective solution has been found that can make non-graphite carbon materials take into account both good rate performance and cycle stability. Summary of the invention

[0003] In view of this, the embodiments of the present application provide a sodium negative electrode material and its application, so that a sodium ion battery using the sodium negative electrode material can have good rate performance, cycle performance, etc.

[0004] A first aspect of an embodiment of the present application provides a sodium battery negative electrode material, comprising a core and a shell layer coated on the core, wherein the core comprises a carbon active material doped with nitrogen; and the shell layer comprises a metal oxide.

[0005] By coating the carbon active material with an outer layer of metal oxide, the number of oxygen-containing functional groups exposed on its surface can be reduced, the interfacial reaction between it and the electrolyte can be inhibited, and the SEI film formed at the negative electrode can be ensured to be dense and stable. Doping the inner core with nitrogen can ensure that the coating of the outer layer of metal oxide does not sacrifice the conductivity of the overall negative electrode material. With the combined effect of the two, the negative electrode material can have good rate performance, high first coulomb efficiency and good cycle performance.

[0006] In the embodiment of the present application, the mass percentage of the metal element in the metal oxide in the sodium negative electrode material is 0.1%-10%. By controlling the mass percentage of the metal element within this range, it is possible to avoid introducing too much metal oxide to reduce the conductivity of the negative electrode material and damage its rate performance while ensuring that there is a sufficient amount of metal oxide to reduce the interface side reaction of the core material.

[0007] In the embodiment of the present application, the mass percentage of the nitrogen element in the sodium negative electrode material is 0.1%-5%. This ensures that the introduced nitrogen element can effectively reduce the effect of reducing the conductivity caused by the introduction of metal oxides, and will not significantly deteriorate the first coulomb efficiency and cycle performance of the composite material.

[0008] In the embodiment of the present application, in the sodium negative electrode material, the metal element in the metal oxide is 2-30 times the mass of the nitrogen element. In this case, the sodium negative electrode material can better balance excellent cycle performance, high first coulomb efficiency and good rate performance.

[0009] In the embodiment of the present application, the thickness of the shell layer is 1nm-20nm. The shell layer of suitable thickness can effectively reduce the interface side reaction between the core and the electrolyte, improve its cycle stability, and will not increase the impedance of the sodium negative electrode material, affect the specific capacity of the core material, etc.

[0010] In the implementation manner of the present application, the nitrogen element is distributed in a surface layer at a certain depth from the surface of the inner core.

[0011] In some embodiments of the present application, the nitrogen element is evenly distributed in the surface layer of the inner core.

[0012] In some other embodiments of the present application, the shell layer partially covers the surface of the core, and the nitrogen element is distributed in the surface area of ​​the core that is not covered by the shell layer material. Further, the coverage rate of the shell layer on the surface of the core is 60%-95%. In this way, the shell layer can effectively inhibit the occurrence of interface side reactions of the core material, thereby better improving its cycle performance.

[0013] The second aspect of the embodiment of the present application provides a sodium ion battery, the sodium ion battery comprising a negative electrode, a separator and a positive electrode, wherein the negative electrode comprises the sodium negative electrode material described in the first aspect of the embodiment of the present application. Since the sodium ion battery uses the above-mentioned sodium negative electrode material, the battery has a high first coulombic efficiency, good cycle performance and excellent rate performance.

[0014] The third aspect of the embodiment of the present application provides an electronic device, which includes a housing and the sodium ion battery as described in the second aspect of the embodiment of the present application, wherein the sodium ion battery is installed in the housing. By adopting the sodium ion battery provided in the embodiment of the present application, the electronic device has improved product performance and outstanding market competitiveness.

[0015] A fourth aspect of an embodiment of the present application provides a battery pack, comprising a plurality of sodium ion batteries as described in the second aspect of the embodiment of the present application, wherein any two of the plurality of sodium ion batteries are connected in series or in parallel.

[0016] A fifth aspect of an embodiment of the present application provides an energy storage system, which includes a power converter and at least one battery pack as described in the fourth aspect of the embodiment of the present application; wherein the power converter is electrically connected to the battery pack, and the power converter is used to convert the voltage output by the battery pack into power and output it to a power grid or a load, and / or to convert the voltage output by an external power supply into power and output it to the battery pack. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A schematic diagram of the structure of a sodium ion battery provided in an embodiment of the present application.

[0018] Figure 2 Two exemplary structural schematic diagrams of sodium battery negative electrode materials provided in the embodiments of the present application are shown.

[0019] Figure 3 A schematic diagram of the structure of an electronic device provided in an embodiment of the present application.

[0020] Figure 4 A schematic diagram of the structure of a battery provided in an embodiment of the present application.

[0021] Figure 5 A schematic diagram of an application scenario of an energy storage system with a battery pack according to an embodiment of the present application is shown.

[0022] Figure 6 The rate performance test results of button-type sodium batteries of Example 1 of the present application and Comparative Examples 1-3 are summarized. DETAILED DESCRIPTION

[0023] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.

[0024] In order to facilitate understanding of the sodium battery negative electrode material and its application provided in the embodiments of the present application, its application scenario is first introduced below. Figure 1 A schematic diagram of the structure of a sodium ion battery is shown as an example. Figure 1 As shown, the sodium ion battery 100 includes a positive electrode 101, a negative electrode 102, a separator 103, an electrolyte 104, and corresponding connecting accessories and circuits. Among them, the separator 103 is located between the positive electrode 101 and the negative electrode 102, and the positive electrode 101, the negative electrode 102, and the separator 103 are immersed in the electrolyte 104; the positive electrode 101 and the negative electrode 102 each include active sodium ions (i.e., Na + ) to achieve energy storage and release of active materials. During the charging process of the sodium ion battery 100, under the action of the external circuit, Na +Electrons are released from the positive electrode 101 and migrate to the negative electrode 102 through the separator 103. At the same time, the electrons flow from the positive electrode to the negative electrode through the external circuit, and the electrical energy is stored. The discharge process is the opposite of the charging process. + The electrons escape from the negative electrode 102 and migrate back to the positive electrode 101 through the separator 103. At the same time, the electrons migrate from the negative electrode to the positive electrode through the external circuit and release electrical energy to the outside. In order to make the sodium ion battery 100 have good rate performance, high first coulomb efficiency, good cycle stability, etc., the embodiment of the present application provides a negative electrode material that can be used for the negative electrode 102 in the sodium ion battery 100.

[0025] See also Figure 2 , which is an exemplary structural diagram of the sodium negative electrode material provided in the embodiment of the present application. Specifically, the sodium negative electrode material 200 provided in the embodiment of the present application includes a core 20 and a shell 21 coated on the core 20, wherein the core 20 includes a carbon active material doped with nitrogen element 201, and the shell 21 includes a metal oxide.

[0026] The above-mentioned sodium negative electrode material 200 is subjected to nitrogen doping and surface coating of metal oxides on the carbon active material, wherein the coating of metal oxides can reduce the number of oxygen-containing functional groups exposed on the surface of the carbon active material and reduce the interfacial side reactions between the carbon active material and the electrolyte, thereby improving its initial coulombic efficiency and cycle performance, and the metal oxide consumes the HF generated by the hydrolysis of the fluorine-containing electrolyte salt in the electrolyte to form metal fluorides, which help to improve the density and stability of the SEI film formed on the surface of the negative electrode and ensure that the thickness of the SEI film is relatively thin, which can also improve the cycle performance of the material and is also helpful to improve the rate performance; and nitrogen doping can improve the conductivity and sodium storage capacity of the inner core surface layer, ensure that the metal oxide coating will not excessively affect the conductivity of the overall composite material, and further improve its rate performance.

[0027] In addition, from another perspective, the above-mentioned nitrogen doping and metal oxide coating are equivalent to forming a modified layer with good conductivity and interface protection on the outside of the undoped carbon active material, which is conducive to the formation of a dense, stable and thin SEI film on the surface of the negative electrode, and ensures its own high conductivity, so that the overall negative electrode material has a high first coulombic efficiency, good rate performance and good cycle performance.

[0028] In this application, the carbon active material is a de / intercalation active Na + The negative electrode active material that realizes energy storage and release is one of the core constituent materials of the sodium negative electrode material 200. The carbon active material is a non-graphite carbon active material, which may specifically include hard carbon material and / or soft carbon material. Non-graphite carbon material is a negative electrode active material suitable for sodium ion batteries.

[0029] In the present application, metal oxide is used as the outer coating material of the above-mentioned negative electrode material, which is basically free of Na removal / insertion. + Inert material. The metal element in the metal oxide can be a metal element with stable ion valence and almost no valence change ability. In the embodiment of the present application, the metal oxide includes one or more of aluminum oxide (Al2O3), copper oxide (CuO), zinc oxide (ZnO), magnesium oxide (MgO), titanium oxide (TiO2), zirconium oxide (ZrO2), and tin oxide (SnO2), but is not limited thereto.

[0030] In the sodium-based negative electrode material 200 of the present application, the core material is the main material that can play an energy storage role, its mass proportion is relatively high, and the shell material mass proportion is relatively low, so as to ensure that the specific capacity of the negative electrode material is relatively high. In the embodiment of the present application, the mass proportion of the metal element and the nitrogen element in the metal oxide in the sodium-based negative electrode material 200 is less than the mass proportion of the carbon element in the sodium-based negative electrode material 200. In addition, the mass proportion of the metal oxide in the sodium-based negative electrode material 200 is less than the mass proportion of the carbon element in the sodium-based negative electrode material 200. Among them, the mass proportion of the carbon element in the sodium-based negative electrode material 200 can be above 76.1%, and further can be above 90%, for example, in the range of 90-99%.

[0031] In the embodiment of the present application, the mass percentage of the metal element in the metal oxide in the sodium negative electrode material 200 is 0.1%-10%, for example, specifically 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 9.5%. Among them, by controlling the mass proportion of the metal element within this range, it is possible to avoid introducing too much metal oxide to reduce the conductivity of the negative electrode material and damage its rate performance while ensuring that there is a sufficient amount of metal oxide to reduce the interface side reaction of the core material. In some embodiments, the mass percentage of the metal element in the metal oxide in the sodium negative electrode material 200 is 0.5%-5%.

[0032] In the embodiment of the present application, the mass percentage of nitrogen element 201 in the sodium negative electrode material 200 is 0.1%-5%, for example, specifically 0.15%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, etc. Among them, controlling the mass proportion of the doped nitrogen element in the carbon active material in the overall composite material to the above range can ensure that the introduced nitrogen element can effectively reduce the effect of reducing the conductivity caused by the introduction of metal oxides, and at the same time will not significantly deteriorate the first coulomb efficiency and cycle performance of the composite material. In some embodiments, the mass percentage of nitrogen element in the sodium negative electrode material 200 is 0.1%-4%, and can further be 0.2%-3%, etc.

[0033] In some embodiments of the present application, in the sodium negative electrode material 200, the metal element is 2-30 times the mass of the nitrogen element. When the content of the nitrogen element or the metal element is close, the mass ratio of the two elements is controlled to satisfy the above relationship, so that the sodium negative electrode material 200 can better balance the excellent cycle performance, the high first coulomb efficiency and the good rate performance, and the comprehensive performance is better.

[0034] In the implementation mode of this application, see the above Figure 2 Middle (A) and Figure 2 In (B), the nitrogen element 201 is distributed in the surface layer at a certain depth (which can be recorded as h) from the surface of the inner core 20. That is, the inner core within the range of 0 to h from the surface of the inner core 20 belongs to the surface layer of the inner core 20. Among them, h is less than or equal to 10nm. The constituent materials of the inner core 20 include nitrogen-doped carbon active materials and undoped carbon active materials, wherein the nitrogen-doped carbon active materials (also known as nitrogen elements) are only distributed in the surface layer of the inner core 20. In other words, the inner core 20 can be regarded as two parts-an inner layer and a surface layer, wherein the constituent material of the inner layer is an undoped carbon active material, and the constituent material of the surface layer includes nitrogen-doped carbon active materials and undoped carbon active materials. In the embodiment of the present application, the depth of the surface layer (that is, the thickness of the surface layer, the doping depth of the nitrogen element) is in the range of 1-10nm.

[0035] In the embodiment of the present application, the thickness of the shell 21 (that is, the thickness of the metal oxide coating layer) is 1nm-20nm. Among them, the shell 21 of suitable thickness can effectively protect the core material, reduce the interface side reaction between the core and the electrolyte, and improve its cycle stability, and will not increase the impedance of the sodium negative electrode material 200 due to the excessive thickness of the shell 21, affect the specific capacity of the core material, and reduce the energy density of the sodium battery. Specifically, the thickness of the shell 21 can be specifically 1.5nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 19.5nm, etc.

[0036] In some embodiments, Figure 2 As shown in (A), the surface layer of the core 20 is uniformly distributed with doped nitrogen elements 201. Figure 2 The sodium negative electrode material 200 shown in (A) can be obtained by first nitrogen doping the carbon active material and then coating it with a metal oxide. It should be noted that Figure 2Although the shell layer 21 completely covers the core 20 in (A), it can be understood that in other embodiments of the present application, the shell layer 21 can also partially cover the surface of the core 20.

[0037] In other embodiments, Figure 2 As shown in (B), the surface of the core 20 is partially covered by the shell 21 (that is, the shell 21 partially covers the surface of the core 10), and the nitrogen element 201 is distributed in the surface area of ​​the core 20 not covered by the shell 21. That is, the nitrogen element is not distributed in the entire surface area of ​​the core, but is only distributed in the surface area not covered by the shell material. Figure 2 The sodium negative electrode material 200 shown in (B) can be obtained by first partially coating the carbon active material with metal oxide and then performing nitrogen doping treatment.

[0038] Furthermore, for Figure 2 In the case shown in (B), the coverage of the shell 21 on the surface of the core 20 can be 60%-95%, for example, 65%, 70%, 75%, 80%, 85%, 90%, 92%, etc. The coverage of the shell 21 on the surface of the core 20 is high enough to ensure that it has a strong effect in inhibiting the interfacial side reactions of the core material. The coverage refers to the ratio of the core surface area covered by the shell material to the total surface area of ​​the core in a single particle of the sodium negative electrode material 200. It should be noted that Figure 2 Although partial coating is illustrated in (B) by discontinuously coating the surface of the inner core 20 with the shell material, it is understandable that the shell material may also continuously cover a portion of the surface of the inner core 20, which should also be regarded as partial coating.

[0039] In addition, for the above Figure 2 In the case of the negative electrode material product in which nitrogen is uniformly distributed on the surface of the core 20 in the example (A), the coverage of the shell 21 on the surface of the core 20 can be 60%-100%, and further can be 60%-95%. When the coverage is less than 100%, the shell material can be distributed at intervals on the surface of the core 20 (such as Figure 2 (B)), or continuously covers a portion of the surface of the core 20.

[0040] The present application also provides a sodium ion battery, which includes the sodium negative electrode material 200, specifically, the negative electrode 102 includes the sodium negative electrode material 200. The exemplary structure of the sodium ion battery can be found in the previous description of the present application. Figure 1 Description.

[0041] Since the sodium ion battery 100 uses the above-mentioned sodium negative electrode material 200 as the negative electrode active material, the battery has a higher initial coulombic efficiency, better cycle performance at room temperature and high temperature, and better rate performance (which can be reflected by the discharge specific capacity values ​​at different discharge rates).

[0042] Among them, the negative electrode 102 generally includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, and the negative electrode active material layer includes a sodium negative electrode material 200 and a binder. In some embodiments, the negative electrode active material layer may also include a conductive agent. The positive electrode current collector, the binder, and the conductive agent may be conventional choices in the field of sodium batteries. For example, the negative electrode current collector may be a copper foil, a carbon-coated copper foil, a copper-plated polymer film, and the like. The binder may include, but is not limited to, one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyacrylamide (PAM), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and sodium alginate. The conductive agent specifically includes, but is not limited to, one or more of acetylene black, Ketjen black, Super P conductive carbon black, graphene, carbon nanotubes, carbon fibers, amorphous carbon, and the like.

[0043] Similar to the structure of the negative electrode 102, the positive electrode 101 includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, the positive electrode active material layer comprising a positive electrode active material, as well as a binder and a conductive agent. Among them, the positive electrode current collector can be aluminum foil, carbon-coated aluminum foil, aluminum-plated polymer film, etc. The separator 103 can be a polymer separator, a non-woven fabric, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and three-layer PP / PE / PP separators. The electrolyte 104 includes an electrolyte sodium salt, a non-aqueous organic solvent, and optional additives (such as film-forming additives, flame retardants, anti-overcharge additives, etc.).

[0044] The sodium ion battery of the embodiment of the present application can be used in terminal consumer products, such as mobile phones, tablet computers, laptops, portable computers, mobile power supplies, and other wearable electronic devices or portable electronic devices, etc., to improve the performance of the products; it can also be used in automobiles, energy storage systems, etc.

[0045] An embodiment of the present application also provides an electronic device, which includes the sodium ion battery 100 using the sodium negative electrode material 200 described above.

[0046] Figure 3 Schematic diagram of the structure of an electronic device provided in some embodiments of the present application. Figure 3As shown, the electronic device 300 includes a housing 301 and a battery 302 installed in the housing 301. The battery 302 includes the sodium ion battery 100 described above in the embodiment of the present application, and the battery 302 supplies power to the electronic device 300. In some embodiments, the housing 301 may include a front cover assembled on the front side of the electronic device and a rear housing assembled on the rear side, and the battery 302 may be fixed inside the rear housing. Figure 3 The electronic device 300 shown may specifically be a mobile phone or the like.

[0047] The electronic device provided in the embodiment of the present application adopts the sodium battery negative electrode material 200 provided in the embodiment of the present application as the negative electrode active material of the battery therein, which can meet the requirements of various electronic devices for long cycle life, good rate performance, etc. of the battery, and improve the user experience and market competitiveness of the electronic equipment.

[0048] An embodiment of the present application further provides a battery pack, which includes a plurality of the above-mentioned sodium ion batteries of the embodiment of the present application, and any two of the plurality of sodium ion batteries are connected in series or in parallel.

[0049] See also Figure 4 , Figure 4 An exemplary structure of a battery pack provided in an embodiment of the present application. Figure 4 As shown, the battery pack 400 includes a battery pack 41, which can be a module formed by connecting multiple sodium ion batteries 100 in series, in parallel or in combination thereof, and any two of the multiple sodium ion batteries 100 are connected in series or in parallel. The battery pack 400 also includes a battery management system (BMS) 42, which can be electrically connected to the battery pack 41. The BMS 42 can be used to monitor the status information of each sodium ion battery 100 in the battery pack 41, such as temperature, voltage, current, internal resistance, etc., and control the charge / discharge status of each sodium ion battery 100. The BMS 42 can include a detector and a controller.

[0050] An embodiment of the present application also provides an energy storage system, which includes a power converter and at least one of the above-mentioned battery packs of an embodiment of the present application. Figure 5 The following is a schematic diagram showing an application scenario of the energy storage system 500 in an embodiment. Figure 5 As shown, the energy storage system 500 is connected between an external power source 510 and a power grid 530 / external load 540 .

[0051] Among them, the external power supply 510 can be a power supply that outputs electric energy in a unidirectional manner, and the power supply can be a power supply in a narrow sense, or the power supply can include a narrow power supply and a power converter. Alternatively, the external power supply 510 can be a battery that can both output electric energy and receive and store electric energy. The external power supply 510 can output direct current or alternating current. For example, the external power supply 510 can be a direct current source including a plurality of photovoltaic components, and the photovoltaic components in the external power supply 510 can form a photovoltaic string in series and / or in parallel, and a plurality of photovoltaic strings can also be connected in parallel to form a photovoltaic array. The external load 540 can be a direct current load or an alternating current load.

[0052] like Figure 5 As shown, the energy storage system 500 may include a power converter 521, a battery pack 400 and a power converter 522 connected in sequence, the power converter 521 may be connected to an external power source 510, and the power converter 522 may be connected to a power grid 530 / external load 540. Both the power converter 521 and the power converter 522 may include a controller and a conversion circuit. The controller is used to control the operation of the conversion circuit, and the conversion circuit is used to perform power conversion, and the power conversion includes but is not limited to voltage conversion, conversion between alternating current and direct current (AC / DC or DC / AC), and conversion between direct current and direct current (DC / DC).

[0053] like Figure 5 As shown, in one embodiment, the external power source 510 may be a DC source, and the power converter 521 may include a DC / DC conversion circuit. The power converter 521 may perform DC / DC conversion on the DC power of the external power source 510 and input it into the battery pack 400 to charge the battery pack 400. The power converter 522 may include a DC / DC conversion circuit. The power converter 522 may perform DC-DC conversion on the DC power output by the battery pack 400 and input it into an external load 540 that uses DC power. Alternatively, the power converter 522 may include a DC / AC conversion circuit. The power converter 522 may perform DC / AC conversion on the DC power output by the battery pack 400 and input it into a power grid 530 or an external load 540 that uses AC power.

[0054] like Figure 5As shown, in another embodiment, the external power source 510 may be an AC source, and the power converter 521 may include an AC / DC conversion circuit. The power converter 521 may perform AC / DC conversion on the AC power of the external power source 510 and input it into the battery pack 400 to charge the battery pack 400. The power converter 522 may include a DC / DC conversion circuit. The power converter 522 may perform DC / DC conversion on the DC power output by the battery pack 400 and input it into an external load 540 that uses DC power. Alternatively, the power converter 522 may include a DC / AC conversion circuit. The power converter 522 may perform DC / AC conversion on the DC power output by the battery pack 400 and input it into the power grid 530 or the external load 540 that uses AC power.

[0055] The embodiments of the present application are further described below with reference to a plurality of embodiments.

[0056] Example 1

[0057] A preparation method of a sodium negative electrode material comprises the following steps:

[0058] (1) Surface nitrogen doping of the hard carbon active material: a certain amount of melamine is mixed with the hard carbon active material, and high-temperature treatment is performed in a nitrogen atmosphere to obtain a nitrogen-doped hard carbon material, wherein the doping amount of nitrogen element is 1%.

[0059] (2) The nitrogen-doped hard carbon material is mixed with a certain concentration of aluminum chloride solution, and then dried and sintered at high temperature to achieve Al2O3 coating on the surface of the nitrogen-doped hard carbon material, thereby obtaining a sodium negative electrode material.

[0060] The sodium negative electrode material prepared in Example 1 includes a core and a shell (specifically an Al2O3 shell) coated on the core, wherein the core includes a hard carbon material doped with nitrogen, and the nitrogen is evenly distributed in a surface layer from the surface of the core to a certain depth inward; the shell thickness is about 2nm. According to elemental analysis, the mass percentage of Al element in the sodium negative electrode material is 2.5%, and the mass percentage of nitrogen element is 0.97%.

[0061] A preparation method of a sodium ion half-cell, comprising:

[0062] (1) Preparation of negative electrode sheet: The sodium battery negative electrode material of Example 1 is mixed with a conductive agent (specifically Super P conductive carbon black) and a binder PVDF in a mass ratio of 80:10:10, and an appropriate amount of N-methylpyrrolidone (NMP) is added and stirred to obtain a negative electrode slurry; the negative electrode slurry is coated on the surface of a negative electrode collector (specifically copper foil) by an extrusion coating process, and a negative electrode sheet is obtained after drying and rolling.

[0063] (2) Assembly of half-cell: In an argon-protected glove box, a sodium metal sheet was used as the counter electrode of the above-mentioned negative electrode sheet, and a 1M NaClO4 EC / PC (EC (ethylene carbonate) and PC (propylene carbonate) volume ratio 1:1) solution was used as the electrolyte to assemble the negative electrode sheet and the sodium metal sheet into a button cell. The electrochemical performance of the button cell can be tested later.

[0064] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples 1-3 are provided.

[0065] Comparative Example 1

[0066] The hard carbon material without doping or coating is directly used as the negative electrode active material of the sodium battery.

[0067] According to the method described in Example 1, the hard carbon material was prepared into a button-type sodium battery.

[0068] Comparative Example 2

[0069] A sodium negative electrode material is a hard carbon material coated with Al2O3 on the surface, wherein the mass percentage of Al element in the material is 2.5%. The difference between the preparation method of the negative electrode material and the above-mentioned embodiment 1 is that the hard carbon active material is directly subjected to the same coating treatment as step (2) in embodiment 1.

[0070] According to the method described in Example 1, the sodium negative electrode material provided in Comparative Example 2 was prepared into a button-type sodium battery.

[0071] Comparative Example 3

[0072] A sodium negative electrode material is a hard carbon material with a surface layer doped with nitrogen, wherein the doping amount of nitrogen is 1%. The difference between the preparation method of the negative electrode material and the above-mentioned embodiment 1 is that the coating treatment in step (2) is not performed.

[0073] According to the method described in Example 1, the sodium negative electrode material provided in Comparative Example 3 was prepared into a button-type sodium battery.

[0074] In order to further strongly support the beneficial effects of the embodiments of the present application, the button-type sodium batteries assembled in the above comparative examples and embodiment 1 were subjected to the following electrochemical performance tests:

[0075] a) First cycle coulombic efficiency and cycle performance at room temperature (25°C): Each button sodium battery was charged and discharged at a current density of 0.1A / g at 25°C, with a voltage range of 2.0-4.0V, and the discharge gram capacity at each cycle number was recorded. Among them, the discharge gram capacity at each cycle number is equal to the ratio of the discharge capacity after the corresponding number of cycles to the mass of the negative electrode active material in the button sodium battery; the first cycle coulombic efficiency is equal to the ratio of the first cycle discharge gram capacity to the first cycle charge gram capacity; the capacity retention rate after a certain number of cycles (such as 100 cycles) is equal to the ratio of the discharge gram capacity after 100 cycles to the first discharge gram capacity. The relevant results are summarized in Table 1.

[0076] b) Cycling performance at high temperature (45°C): The cycling performance test of each button sodium battery at high temperature can refer to the test in item a) above. The relevant results are summarized in Table 1.

[0077] c) Rate performance test: The above button cells were tested at a rate of 0.1A / g at 25°C. Each cell was charged at a current density of 0.1A / g and discharged at current densities of 0.05A / g, 0.1mA / g, 0.2A / g, 0.5A / g, 1A / g, and 0.05A / g. The relevant results are summarized in Figure 6 middle.

[0078] Table 1 Comparison of first cycle coulombic efficiency and cycle performance of button-type sodium batteries of Example 1 and Comparative Examples 1-3

[0079]

[0080] From Table 1 and Figure 6 It can be known that Example 1 of the present application performs surface nitrogen doping and external metal oxide coating on the hard carbon material, which not only improves the first-cycle coulomb efficiency and improves the cycle performance, but also significantly improves the rate performance of the material. While Comparative Example 2 simply coats the hard carbon material with metal oxide, although it can improve the first-cycle coulomb efficiency and cycle performance of the material to a certain extent, the improvement in rate performance is not obvious, especially the discharge gram capacity of the battery in Comparative Example 2 when discharged above 0.5A is low: while Comparative Example 3 simply performs nitrogen doping on the hard carbon material, although it will improve the conductivity to a certain extent, thereby improving the rate performance, it will reduce the first-cycle coulomb efficiency of the material and deteriorate the cycle performance, which is lower than that of the untreated Comparative Example 1.

[0081] Example 2

[0082] A preparation method of a sodium negative electrode material comprises the following steps:

[0083] (1) mixing and stirring a hard carbon active material with a certain concentration of aluminum chloride solution, drying, and high-temperature sintering to achieve surface coating with Al2O3 to obtain a core-shell type material, wherein the Al2O3 coating layer is discontinuously coated on the surface of the hard carbon material, with a coverage rate of 70%;

[0084] (2) Nitrogen doping of the core-shell material: mixing the material with a certain amount of melamine, and then subjecting the mixture to high temperature treatment in a nitrogen atmosphere to obtain a sodium negative electrode material.

[0085] The sodium negative electrode material prepared in Example 2 includes a core and an Al2O3 shell layer discontinuously coated on the core, wherein the core includes a hard carbon material doped with nitrogen, and the nitrogen element is distributed in a surface area of ​​the core that is not covered by the Al2O3 material, and the depth of the surface layer is about 2nm; the thickness of the Al2O3 shell layer is 2nm. In the sodium negative electrode material, the mass percentage of the Al element is 2%, and the mass percentage of the nitrogen element is 0.5%.

[0086] Example 3

[0087] A sodium negative electrode material, which is mainly different from Example 1 in that: in the sodium negative electrode material, the mass percentage of Al element is 10%, the mass percentage of nitrogen element is 0.5%; and the thickness of the shell layer is 20nm.

[0088] Example 4

[0089] A sodium negative electrode material, which is mainly different from Example 1 in that: in the sodium negative electrode material, the mass percentage of Al element is 0.5%, the mass percentage of nitrogen element is 0.1%; and the thickness of the shell layer is 1 nm.

[0090] Example 5

[0091] A sodium negative electrode material, which is mainly different from Example 1 in that: in the sodium negative electrode material, the mass percentage of Al element is 5%, and the mass percentage of nitrogen element is 0.1%.

[0092] Example 6

[0093] A sodium negative electrode material, which differs from Example 1 in that: in the sodium negative electrode material, the mass percentage of Al element is 2%, and the mass percentage of nitrogen element is 5%.

[0094] According to the method described in Example 1, the sodium negative electrode materials provided in Examples 2-6 were respectively prepared into button-type sodium batteries. Table 2 below summarizes the relevant test results of the sodium button-type batteries of Examples 1-6.

[0095] Table 2

[0096]

[0097] It can be seen from Table 2 that, compared with the untreated hard carbon active material (Comparative Example 1), the sodium battery made of the sodium negative electrode material provided in the embodiment of the present application has better comprehensive performance, and can better balance the high first coulomb efficiency, good cycle performance (reflected by the discharge gram capacity and cycle capacity retention rate after 100 cycles in Table 2), capacity retention rate and rate performance (rate performance is reflected by the discharge gram capacity under a large current of 1A in Table 2). In addition, when the nitrogen doping content in the sodium negative electrode material of the embodiment of the present application is close, but the mass ratio of the metal element derived from the coating layer material to the doped nitrogen element is not in the range of 2-30 (such as Example 5), the improvement effect on the rate performance of the sodium battery is slightly worse than that of Example 4.

[0098] The above only expresses several exemplary embodiments of the present application, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present application. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be based on the attached claims.

[0099] It should be understood that the first, second and various numerical numbers involved in this document are only distinguished for the convenience of description and are not used to limit the scope of the present application.

[0100] In this application, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0101] In the present application, "at least one" means one or more, and "more than one" means greater than or equal to two. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple, respectively.

Claims

1. A sodium negative electrode material, characterized in that: The sodium negative electrode material comprises a core and a shell layer coated on the core, wherein the core comprises a carbon active material doped with nitrogen; and the shell layer comprises a metal oxide.

2. The sodium negative electrode material according to claim 1, characterized in that The mass proportion of the metal element in the metal oxide in the sodium negative electrode material is less than the mass proportion of the carbon element in the sodium negative electrode material.

3. The sodium negative electrode material according to claim 1 or 2, characterized in that: The mass percentage of the metal element in the metal oxide in the sodium negative electrode material is 0.1%-10%.

4. The sodium negative electrode material according to any one of claims 1 to 3, characterized in that The mass percentage of the nitrogen element in the sodium negative electrode material is 0.1%-5%.

5. The sodium negative electrode material according to any one of claims 1 to 4, characterized in that: In the sodium negative electrode material, the mass of the metal element in the metal oxide is 2-30 times that of the nitrogen element.

6. The sodium negative electrode material according to any one of claims 1 to 5, characterized in that: The metal oxide includes one or more of aluminum oxide, copper oxide, zinc oxide, magnesium oxide, titanium oxide, zirconium oxide, and tin oxide.

7. The sodium negative electrode material according to any one of claims 1 to 6, characterized in that: The nitrogen element is distributed in the surface layer of the inner core, and the depth of the surface layer does not exceed 10 nm.

8. The sodium negative electrode material according to claim 7, characterized in that The nitrogen element is evenly distributed in the surface layer of the inner core.

9. The sodium negative electrode material according to claim 7, characterized in that The shell layer partially covers the surface of the core, and the nitrogen element is distributed in the surface area of ​​the core that is not covered by the shell layer material.

10. The sodium negative electrode material according to claim 9, characterized in that: The coverage rate of the shell layer on the surface of the core is 60%-95%.

11. The sodium negative electrode material according to any one of claims 7 to 10, characterized in that: The thickness of the shell layer is 1nm-20nm.

12. A sodium ion battery, characterized in that: The sodium ion battery comprises a negative electrode, a separator and a positive electrode, wherein the negative electrode comprises the sodium negative electrode material according to any one of claims 1 to 11.

13. An electronic device, characterized in that: The electronic device comprises a housing and the sodium ion battery as claimed in claim 12, wherein the sodium ion battery is installed in the housing.

14. A battery pack, characterized in that: The battery pack comprises a plurality of sodium ion batteries as claimed in claim 12, and any two of the plurality of sodium ion batteries are connected in series or in parallel.

15. An energy storage system, characterized in that: The energy storage system comprises a power converter and at least one battery pack as claimed in claim 12; Among them, the power converter is electrically connected to the battery pack, and the power converter is used to convert the voltage output by the battery pack into power and output it to the power grid or load, and / or to convert the voltage output by an external power supply into power and output it to the battery pack.